EFFECT OF GREEN PROCUREMENT PRACTICES ON COMPETITIVENESS OF MANUFACTURING FIRMS IN KENYA: A CASE OF UNILEVER KENYA LIMITED - Kimira, Catherine Wangui; Getuno, Dr. Pamela; Kiarie, Dr. David (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
An increasing number of companies are recognizing environmental consciousness as mandatory business imperative. Firms are incorporating green procurement into their daily operations across industries; however, not all firms pursue green procurement initiatives and as such they may not know the impact it has on their organization. The general objective of this study was to determine the effect of green procurement practices on competitiveness of manufacturing firms in Kenya: a case of Unilever Kenya Limited. The study specifically sought to determine the effect of supplier selection, product contents, procurement process and ethical practices on competitiveness of Unilever Kenya Limited. The study adopted descriptive research design. The target population was 60 managers in Unilever Kenya Limited who includes the senior management, middle level managers and lower level managers. Since the population was small, a census study was adopted whereby the entire population of 60 managers formed the sample size for the study. The study collected primary data using a questionnaire. A pilot test was conducted to test for validity and reliability of the data collection tool. Both descriptive and inferential statistics were adopted for analysis. Descriptive statistics included frequency distribution tables, mean and standard deviation while inferential statistics entailed regression analysis. Data was presented using tables, charts and graphs. The study found out that selection of suppliers, procurement of products with less harmful contents, green procurement processes and green logistics influenced competitiveness of the company to a great extent. The study found out that there was a positive and statistically significant relationship between firm competitiveness and green products; green procurement processes; green logistics. The study concludes that Unilever Kenya had embraced green procurement practices among them selection of suppliers are “green” or have adopted green procurement. The company ensured that it adhered to environmental standards and quality control measures to ensure that the products procured are of quality. The study also concludes that Unilever Company had adopted green procurement processes such as the 3Rs and paperless procurement. The green logistics also provided flexible and efficient physical distribution systems to the company; and enhanced reliable and on-time distribution of goods to the market with less environmental damage. The study recommends that organizations should put more effort to develop suppliers into more strategic partners in the supply chain. The managers need to realize that green procurement alone cannot help in improving supplier performance. Instead, focal firms are crucial for improving downstream capabilities of suppliers.